ANTI-INFLAMMATORY, FREE RADICAL SCAVENGING AND CALCIUM ANTAGONIST ACTIVITIES OF CORCHORUS FASCICULARIS LAM. CRUDE EXTRACT - K. H. Janbaz; U. Zia; M. H. Mehmood; S. Bashir; M. I. Choudhary; A. H. Gilani (Journal of Animal and Plant Sciences, 2012)
The plants of genus Corchorus have a folkloric repute to possess anti-inflammatory activity. The crude ethanolic extract of Corchorus fascicularis Lam. (CFE) was screened for presence of anti-inflammatory, free radical scavenging and calcium channel blocking (CCB) activities to validate its vernacular use. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay was used to assess free radical scavenging activity, anti-inflammatory potential was estimated through inhibitory effect on carrageenin-induced rat paw edema, whereas calcium channel blocking (CCB) effect was explored on isolated rabbit jejunum preparations. The CFE (50 and 100 mg/kg) administration resulted in a significant (P < 0.05) decrease in rat paw edema similar to aspirin, while a concentration-dependant (IC50: 95.91 ± 3.07 µg/ml) inhibition of DPPH was achieved in a manner comparable to propylgallate (standard). The CCB-like effect was evidenced as CFE exhibited a concentration-dependant (0.01–1 mg/ml) non-specific relaxant effect in rabbit jejunum, which was supported further by a rightward shift of the Ca++ concentration-response curves, similar to verapamil. These results indicated presence of free radical scavenging, anti-inflammatory and CCB activities in Corchorus fascicularis and may be attributed to the possible presence of flavonoids and tannins among the plant constituents. The present study thus validates the folkloric use of Corchorus fascicularis in inflammatory diseases.
Keywords: Corchorus fascicularis; Anti-inflammatory; DPPH scavenging; Calcium antagonist.